Online Safty concerns' influence on women's satisfaction with social media - Mohammad, Anber Abraheem Shlash; C V, Prasad; Raja, N; M P, Bindu Menon; Vasudevan, Asokan (International Journal of Innovative Research and Scientific Studies, 2025)
As social media becomes more integrated into daily life, knowing the elements that influence customer satisfaction is critical, especially for women who may face specific problems. This study investigates how online safety concerns affect women's satisfaction with social media, focusing on five key factors such as “Risk of Cyber Harassment (RH)”, “Privacy Concerns (PC)”, “Digital Literacy and Skills Gap (DS)”, “Cybersecurity Awareness and Training (CT)”, and “Representation and Inclusivity in Digital Media (RI)”. Multi-stage stratified random sampling ensures reliable and statistically sound results. The survey included 320 women respondents from the north, central, and south zones of Kerala: Kozhikode from the north, Trissur from the central region, and Trivandrum from the south zone. The chi-square test was performed to assess how demographic characteristics affect women's enjoyment of social media. The computed regression model in our study has a sufficient goodness of fit, particularly when it comes to predicting the variation in women’s satisfaction with social media, with a value of 53.788. The multiple regression model reveals that all six factors significantly influenced overall satisfaction. Using a multiple regression model, we show that both the risk of cyber harassment and privacy concerns have a negative impact on women's satisfaction with social media, with effect coefficients of -0.36 and -0.29, respectively. In contrast, online safety awareness and training had the greatest positive impact on satisfaction, with a value of 0.51. These findings indicate that, while concerns about harassment and privacy might detract from satisfaction, more training greatly increases it. The study highlights the importance of addressing these factors to increase women's enjoyment and participation in social media environments.